2013
DOI: 10.1038/nchem.1776
|View full text |Cite
|
Sign up to set email alerts
|

A boron–boron coupling reaction between two ethyl cation analogues

Abstract: The design of larger architectures from smaller molecular building blocks by element-element coupling reactions is one of the key concerns of synthetic chemistry, so a number of strategies were developed for this bottom-up approach. A general scheme is the coupling of two elements with opposing polarity or that of two radicals. Here, we show that a B-B coupling reaction is possible between two boron analogues of the ethyl cation, resulting in the formation of an unprecedented dicationic tetraborane. The bondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0
17

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 29 publications
2
65
0
17
Order By: Relevance
“…The most widely used method is the value of δ 11 B; however, this has limitations and is generally only able to unambiguously distinguish between 3 and 4 coordination at boron. This has recently been supplemented by the use of DOSY experiments, with the difference between anion and cation diffusion coefficients, an established method to assess the degree of ion association in solution [19,20]. This approach was used to confirm the solvent-separated ion pair nature of [BBN(IMes)][OTf], whose existence as a borenium cation demonstrates that with sufficient steric bulk around boron even triflate can fulfil the role of a "non"-coordinating anion towards a borenium cation [19].…”
Section: ) 4 ]mentioning
confidence: 99%
“…The most widely used method is the value of δ 11 B; however, this has limitations and is generally only able to unambiguously distinguish between 3 and 4 coordination at boron. This has recently been supplemented by the use of DOSY experiments, with the difference between anion and cation diffusion coefficients, an established method to assess the degree of ion association in solution [19,20]. This approach was used to confirm the solvent-separated ion pair nature of [BBN(IMes)][OTf], whose existence as a borenium cation demonstrates that with sufficient steric bulk around boron even triflate can fulfil the role of a "non"-coordinating anion towards a borenium cation [19].…”
Section: ) 4 ]mentioning
confidence: 99%
“…[18] A starting reagent in our research in this area is the diborane [HB(hpp)] 2 (2; see Scheme 2, a; hpp = 1,3,4,6,7,8-hexahydro-2H-pyrimido[1,2-a]pyrimidinate), which can be synthesized in high yield in a one-pot reaction from commercially available hppH and H 3 BǟNMe 3 (see Scheme 2,a). [20][21][22][23] We recently showed that hydride abstraction from [HB(hpp)] 2 (2) with B(C 6 F 5 ) 3 [24] results in the formation of the dication [H 2 B 4 (hpp) 4 ] 2+ (3) with a four-electron, fourcenter bond between the four boron atoms (see Scheme 2,b work, it was not possible to capture the postulated intermediate cation 4, which is isolobal to the ethyl cation. As opposed to the "nonclassical" structure with one bridging hydrogen atom of the ethyl cation, [25,26] quantum chemical calculations predict that 4 has a terminal B-H bond.…”
Section: Introductionmentioning
confidence: 98%
“…As opposed to the "nonclassical" structure with one bridging hydrogen atom of the ethyl cation, [25,26] quantum chemical calculations predict that 4 has a terminal B-H bond. [24] Moreover, the three-coordinate boron cation is not planar, since the bridging hpp substituents force it into a pyramidal geometry. Herein, we show that 4 can be captured by Lewis bases.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Himmel and co-workers reported the electrophilic activation of a doubly-base-stabilized diborane(4) leading to the discovery of unusual hydride-abstractioninduced boronboron coupling. 65 Treatment of the hpp-bridged diborane(4) (32) 66 with B(C 6 F 5 ) 3 results in the formation of a transient monocation [33] + , which quickly dimerizes through the formation of a new boronboron bond to yield a highly robust dicationic tetranuclear B(II) compound [H 2 B 4 (¯-hpp) 4 ] 2+ ( [34] 2+ ) (Scheme 11). 65 The crystal structure of [34][HB(C 6 F 5 ) 3 ] 2 shows that the central B 4 unit is on the same plane and arranged in a distorted rhombus geometry with a BB distance of 1.703(4) ¡ along the shorter diagonal of the rhombus.…”
Section: ¹1mentioning
confidence: 99%
“…65 Treatment of the hpp-bridged diborane(4) (32) 66 with B(C 6 F 5 ) 3 results in the formation of a transient monocation [33] + , which quickly dimerizes through the formation of a new boronboron bond to yield a highly robust dicationic tetranuclear B(II) compound [H 2 B 4 (¯-hpp) 4 ] 2+ ( [34] 2+ ) (Scheme 11). 65 The crystal structure of [34][HB(C 6 F 5 ) 3 ] 2 shows that the central B 4 unit is on the same plane and arranged in a distorted rhombus geometry with a BB distance of 1.703(4) ¡ along the shorter diagonal of the rhombus. With the remaining BB distances of 1.896(3) and 1.943(3) ¡, the extremely short BB bond length of the central B 2 unit and an acute BBB angle of 65.31 (15)°s uggest the presence of two BBB 3c2e bonds in the central B 4 core.…”
Section: ¹1mentioning
confidence: 99%